Approximate Methods for Generalized Inverses of Operators in Banach Spaces (Journal of Computational Mathematics, 2021)
In this paper, we present the necessary and sufficient condition of convergence of several iterative methods for computing the generalized inverses of operators in Banach spaces. It is proved that the iterative methods converge to the generalized inverse of an Operator in Banach spaces if and only if these conditions are satisfied.